INTERDIGITAL-TYPE CAPACITIVE SENSOR FOR EXCESSIVE SKIN MOISTURE CONTENT DIAGNOSTICS - A. M. Vorobei; D. V. Rymarev; A. L. Potapov; M. V. Davydov; S. S. Stebunov (Приборы и методы измерений)
Interdigital capacitive sensor for excessive skin moisture content was developed.